(untitled) (Baghdad Science Journal, 2020)
Cladosporium sp. plays an important role in human health, it is one of the pathogenic fungi which cause allergy and asthma and most frequently isolated from airborne spores. In this study, a couple of universal PCR primers were designed to identify the pathogenic fungi Cladosporium sp. according to conserved region 5.8S, 18S and 28S subunit ribosomal RNA gene in Cladosporium species. In silico RFLP-PCR were used to identify twenty-four Cladosporium strains. The results showed that the universal primer has the specificity to amplify the conserved region in 24 species as a band in virtual agarose gel. They also showed that the RFLP method is able to identify three Cladosporium species by specific and unique restriction enzymes for each one. These species are Cl. halotorenas by the two unique enzymes BsaXI and MobII, the other species is Cl. colrandse by two enzymes BccI and BtsCI, while the third species is Cl. aciculare by one enzyme BceAI. Each enzyme forms two bands in virtual agarose gel as a results of cutting the DNA by the enzyme, where the rest twenty – two species share more than one restriction enzymes. This method is active and rapid for identifying Cladosporium genus and three species by computational bases methods before applying it in the lab for more accuracy, efficiency, and specificity of designed primer to get good results in a short time.